Healthcare Responses to Gender-Based Violence in Timor-Leste: Women Want Empathy, Information and Safety From an Integrated Support System - Wild, Kayli (Journal of interpersonal violence, 2022)
Healthcare providers are one of the first professionals women are likely to come into contact with after experiencing violence as they seek care for injuries and associated health problems or in routine care such as reproductive health services. Systematic reviews of women's experiences and expectations when disclosing abuse in health settings reveal a dearth of research with women in low-income countries and from rural areas. The aim of this study was to understand the information and interventions women who have experienced domestic violence or sexual assault want from their health providers in Timor-Leste, a country with a largely rural population and very high rates of violence against women. The mixed-methods study consisted of in-depth qualitative interviews with 28 women survivors of violence, followed by a ?pile-sort? activity in which they rated their preference for different types of interventions they wanted from their healthcare provider. The pile-sort activity showed the highest-ranked interventions centred around emotional support, information and safety, the middle-ranked interventions centred around empowering women and playing an advocacy role, and the lowestranked interventions were around intervening at the relationship level and mandatory reporting to the police. The qualitative interviews provided rich insights that affirmed women value empathy and kindness from service providers, they want to be supported to make their own decisions and the importance of formal as well as informal sources of support such as community leaders and family. There are significant implications for the content of existing training programmes on gender-based violence in Timor-Leste and similar contexts, particularly the need to build capacity on how to respond in an empathic and empowering way and how to balance mandatory reporting obligations, while also practising woman-centred care and providing the kind of support women value.